A new species of Neoliomera Odhner, 1925, from the western Pacific, and the first record of N. demani Forest & Guinot, 1961, from Taiwan (Crustacea: Decapoda: Brachyura: Xanthidae) - Ho, P.-H.; Ng, Peter K. L. (Zootaxa, 2014)
A new species of a strikingly coloured xanthid crab of the genus Neoliomera Odhner, 1925, is described from coral reefs in Guam, Taiwan, and the Hawaiian Islands. The new species is allied to N. pubescens (H. Milne Edwards, 1834), and N. demani Forest & Guinot, 1961, but differs in the form of the carapace armature, frontal margin, structure of the chela, proportions of the ambulatory merus and the form of the male first gonopod. Neoliomera demani is also recorded from Taiwan for the first time and aspects of its taxonomy are discussed.